Development Of Student Attendance Record In Akademi Komunitas Negeri Putra Sang Fajar Blitar Using Codeigniter Framework - M Mujiono; Adimas Ketut Nalendra; Rafika Akhsani; Anang Widigdyo (RESEARCH : Journal of Computer, Information System & Technology Management, 2020)
Attendance record and calculation absent is a key success for the the teaching and learning process in college. The process of recording attendance using manual signatures makes it difficult to record absent data. This data is important to see the level of student discipline in taking lectures and is an early detection to monitor student discipline by giving a warning letter. For this reason, it is necessary to make an application for student attendance recording that can calculation absent and warning letters. This application is based on the web and using PHP programming language, Codeigniter framework and MySQL for database. Testing this application using blackbox testing and user questionnaires. The results of the black box testing prove that the functionality provided by the application is functioning properly according to planning. Testing with a questionnaire was carried out by distributing to all lecturers and academic staff are 15 respondents, the results of the questionnaire which were divided got a score of 90% of the respondents who chose that this application helped the presence process and the recording of the number of student absences